Contribution Factors Of Tourism Industry Towards Gdp : A Study In Ten Asian Countries - Chow, Ming Yan (2014)
This study used secondary data to examine the direct and causal relationships between factors of contribution (number of international tourist arrivals, capital investment, government spending, international tourism receipts and foreign exchange rate) and Gross Domestic Product (GDP) for panel data of ten Asian countries over a period of 1993 - 2003 based on the growth theory (tourism-led economic growth theory, economic-driven tourism growth theory and reciprocal causal theory).A panel regression model with fixed effect model is performed to investigate the direct relationship between factors of contribution and Gross Domestic Product (GDP); the results showed capital investment, government spending and international tourism receipts have positive effect on Gross Domestic Product (GDP). A panel Granger causality test is carried out to examine the direction of causal relationship between factors of contribution and Gross Domestic Product (GOP); the results showed that the number of international tourist arrivals and international tourism receipts have unidirectional causal related to Gross Domestic Product (GDP); Gross Domestic Product (GDP) has unidirectional causal effect on government spending; capital investment and foreign exchange rate have bidirectional causal related to Gross Domestic Product (GDP) respectively.